STRATEGI PENGEMBANGAN BUDIDAYA LEBAH MADU DI KELURAHAN KALAMPANGAN KECAMATAN SABANGAU KOTA PALANGKA RAYA - Yunita, Yunita; Pordamantra, Pordamantra; Berkat A. P. (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
This research is done (1). to identify about the internal and external factors which become the strength, weakness, opportunity, threat by analysis method of IFAS and EFAS; (2). to formulate the alternative strategy that being possible to be applied by SWOT matrix. The results of this research show that (1). internal factors (strengths and weaknesses) and external (opportunities and threats) the development of honey bee cultivation in the Kalampangan Village, that is strength has four variables, among others workforce training, production facilities are available, cultivation management has been implemented and the marketing chain is short. Weakness has two variables, among others lack of group members participation and less attractive product packaging. Opportunities have three variables, that is the government's attention, establishing partnership relations and technological and information development. While threats have three variables, among others competitively priced honey products, weather changes and pest attacks. (2). the alternative strategy which can be applied for the effort of developing honey bee cultivation in the urban village of Kalampangan is the (SO) strategy which means to use the government?s support on spreading product marketing network, and developing cultivation technology of honey bee; the (WO) strategy which means we make a training and associating to improve the skills of the breeder and repairing the product?s packaging; the (ST) strategy which means to maintain the production, and maintain the product?s quality; and the (WT) strategy which means to maintain the group cooperation and to keep the area of woof plants.